Case report: Double-armed flanged polypropylene suture for repairing wide iridodialysis - Peng, Tingting; Guo, Huafang; Wang, Yong; Zhou, Li; Bao, Xianyi (Frontiers in Medicine, 2023)
Purpose: To describe a new technique for repairing wide iridodialysis (>180º) with a double-armed flanged polypropylene suture. Setting: Private practice, Wuhan, China. Design: case report. Methods: Adjacent to the iridodialysis side, the sclera was punctured 2 mm exterior to the corneal limbus into the anterior chamber with a 30-G needle, then the root of the de-inserted iris was punctured. A 7-0 polypropylene thread was placed into the anterior chamber through a corneal incision on the opposite side and inserted into the needle. The needle was withdrawn, leaving one side of the suture out of the eye. Then, the sclera was punctured by a new needle 2 mm from the first puncture site and passed through the iris root 2 mm from the original iris puncture point. The other end of the thread was inserted into the needle and taken out of the eye. The suture was tightened to make the iris root adhere to the corneal limbus. Finally, the suture is was cut, and the ends were cauterized and left inside the sclera. This procedure can be repeated until the iridodialysis is solved. Results: The abovementioned technique was applied in four cases. At the end of the operations, the pupils of all patients were nearly round, with a diameter of about 3 mm. No patient suffered from intraoperative and postoperative complications. Conclusions: The double-armed flanged polypropylene suture is a simple and safe operation method that can be applied to repair wide iridodialysis.